Cyclin‐dependent kinase 8/19 inhibition suppresses osteoclastogenesis by downregulating RANK and promotes osteoblast mineralization and cancellous bone healing. Issue 9 (21st February 2019) - Amirhosseini, Mehdi; Bernhardsson, Magnus; Lång, Pernilla; Andersson, Göran; Flygare, Johan; Fahlgren, Anna
Abstract: Cyclin‐dependent kinase 8 (CDK8) is a mediator complex‐associated transcriptional regulator that acts depending on context and cell type. While primarily under investigation as potential cancer therapeutics, some inhibitors of CDK8—and its paralog CDK19—have been reported to affect the osteoblast lineage and bone formation. This study investigated the effects of two selective CDK8/19 inhibitors on osteoclastogenesis and osteoblasts in vitro, and further evaluated how local treatment with a CDK8/19 inhibitor affects cancellous bone healing in rats. CDK8/19 inhibitors did not alter the proliferation of neither mouse bone marrow–derived macrophages (BMMs) nor primary mouse osteoblasts. Receptor activator of nuclear factor κΒ (NF‐κB) ligand (RANKL)‐induced osteoclastogenesis from mouse BMMs was suppressed markedly by inhibition of CDK8/19, concomitant with reduced tartrate‐resistant acid phosphatase (TRAP) activity and C‐terminal telopeptide of type I collagen levels. This was accompanied by downregulation of PU.1, RANK, NF‐κB, nuclear factor of activated T‐cells 1 (NFATc1), dendritic cell‐specific transmembrane protein (DC‐STAMP), TRAP, and cathepsin K in RANKL‐stimulated BMMs. Downregulating RANK and its downstream signaling in osteoclast precursors enforce CDK8/19 inhibitors as anticatabolic agents to impede excessive osteoclastogenesis. In mouse primary osteoblasts, CDK8/19 inhibition did not affect differentiation but enhanced osteoblast mineralization by promoting alkaline phosphatase activity and downregulating osteopontin, a negative regulator of mineralization. In rat tibiae, a CDK8/19 inhibitor administered locally promoted cancellous bone regeneration. Our data indicate that inhibitors of CDK8/19 have the potential to develop into therapeutics to restrict osteolysis and enhance bone regeneration. Abstract : Inhibition of cyclin‐dependent kinase 8/19 (CDK8/19) suppressed receptor activator of nuclear factor κ‐Β (NF‐κB) ligand (RANKL)‐induced osteoclast differentiation from mouse bone marrow macrophages by disrupting RANK signaling. CDK8/19 inhibition in osteoblasts led to downregulated osteopontin messenger RNA (mRNA), increased alkaline phosphatase activity, and enhanced calcium deposition. Furthermore, local administration of a CDK8/19 inhibitor enhanced bone volume fraction and bone mineral density in a rat model for bone regeneration.